Renovation of industrial enterprises for hotel facilities.Architectural-shaped transformations - Bridnia, Larysa; Zehong, Gong (Wschodnioeuropejskie Czasopismo Naukowe, 2019)
Modern approaches to ensuring the architectural expressiveness of objects during the reconstruction and renovation of industrial enterprises. The main architectural means of their figurative transformation. исследованы современные подходы к обеспечению архитектурной выразительности объектов при реконструкции и реновации промышленных предприятий. Выделены основные архитектурные средства их образной трансформации .
Keywords: renovation; reconstruction; renovation of industrial objects; historical industrial buildings